2016
DOI: 10.1071/an14686
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the nutritive value and aerobic stability of corn silages inoculated with Bacillus subtilis alone or combined with Lactobacillus plantarum

Abstract: Chemical composition, fermentation characteristics, in vitro digestibility and aerobic stability were evaluated in corn silage inoculated with microbial additives in two different experiments. Inoculant treatments (untreated, Bacillus subtilis and B. subtilis combined with Lactobacillus plantarum) were applied to fresh forages. Chopped corn plants (2B655 Hx) were ensiled in laboratory silos for periods of 7, 14, 21 and 63 days to evaluate the fermentation parameters. The experimental silos were weighed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 23 publications
3
41
0
6
Order By: Relevance
“…Man, Rogosa and Sharpe (MRS) agar was used to count LAB by pour plate, whereas potato dextrose agar (PDA) was used to count yeasts and moulds by spread plate. Both MRS and PDA plates were incubated at 28°C according to protocols used in previous studies carried out in our laboratory (Basso et al., ; Lara et al., ; Rabelo, Basso, et al., ). Lactic acid bacteria and yeasts were counted after 2 days, and moulds were counted after 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…Man, Rogosa and Sharpe (MRS) agar was used to count LAB by pour plate, whereas potato dextrose agar (PDA) was used to count yeasts and moulds by spread plate. Both MRS and PDA plates were incubated at 28°C according to protocols used in previous studies carried out in our laboratory (Basso et al., ; Lara et al., ; Rabelo, Basso, et al., ). Lactic acid bacteria and yeasts were counted after 2 days, and moulds were counted after 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…Many species of Bacillus can produce antimicrobial substances as peptide and lipopeptide antibiotics and as bacteriocins, and the bacteriocins of Bacillus have a broader action spectrum than those produced by LAB (Abriouel et al 2011). Positive results include increased aerobic stability with the inoculation of B. subtilis (Lara et al 2015) and the inhibition of moulds by B. subitilis, B. licheniformis and B. pumilus (Pahlow et al 2003). No significant changes were observed in the silage with the inoculation of B. pumilus .…”
Section: Spore-forming Bacteriamentioning
confidence: 98%
“…Bacillus (B) species have been investigated in recent years as novel silage inoculants. Lara et al (2016) found some species from this genus could improve the aerobic stability of silage by producing bacteriocin, which inhibits yeasts and molds. The application of these species in animal feed also exhibited positive effects on feed utilization and livestock growth performance (Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%